2021
DOI: 10.3390/life11100996
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Antimicrobial Resistance: Data from the Greek Electronic System for the Surveillance of Antimicrobial Resistance—WHONET-Greece (January 2018–March 2021)

Abstract: Changes in hospitals’ daily practice due to COVID-19 pandemic may have an impact on antimicrobial resistance (AMR). We aimed to assess this possible impact as captured by the Greek Electronic System for the Surveillance of Antimicrobial Resistance (WHONET-Greece). Routine susceptibility data of 17,837 Gram-negative and Gram-positive bacterial isolates from blood and respiratory specimens of hospitalized patients in nine COVID-19 tertiary hospitals were used in order to identify potential differences in AMR tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 67 publications
3
46
0
Order By: Relevance
“…Another study showed that A. baumannii isolated from endotracheal aspirate samples of nineteen COVID-19 patients was resistant to all tested antibiotics, except colistin with a resistance rate of 52% [ 36 ]. Furthermore, isolated A. baumannii from blood among Greek ICU COVID-19 patients was resistant (100%) to meropenem and amikacin (87.5%), but more sensitive to colistin (47%) and tigecycline (27.5%) [ 51 ]. These surveillance studies indicate that colistin is an active drug against A .…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that A. baumannii isolated from endotracheal aspirate samples of nineteen COVID-19 patients was resistant to all tested antibiotics, except colistin with a resistance rate of 52% [ 36 ]. Furthermore, isolated A. baumannii from blood among Greek ICU COVID-19 patients was resistant (100%) to meropenem and amikacin (87.5%), but more sensitive to colistin (47%) and tigecycline (27.5%) [ 51 ]. These surveillance studies indicate that colistin is an active drug against A .…”
Section: Discussionmentioning
confidence: 99%
“…Considering microbiology, retrospective studies, together with global and national surveillance reports, indicated an increasing number of HAIs during the COVID-19 epidemic [ 15 , 17 , 37 , 38 , 39 , 40 ]. After analyzing HAIs from the National Healthcare Safety Network for 2019 and 2020 by acute-care hospitals, Weiner-Lastinger et al reported a significant increase in the incidence of central-line-associated bloodstream infections, catheter-associated urinary tract infections, ventilator-associated events, and MRSA bacteremia in 2020 in the USA [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…At typical plasma maximum concentrations, an fAUC/MIC of 25 has been linked to 2-log killing in in vitro experiments for Klebsiella pneumoniae [ 23 ], while values of 12.2–22.8 and 7–42 have been found to predict 1-log killing in Pseudomonas aeruginosa and Acinetobacter baumannii animal thigh and lung infection models [ 24 ]. Assuming that these considerations and hypotheses are true, and given the rising MICs to colistin among critically ill patients in endemic environments [ 25 ] (where this inhalational antimicrobial treatment is needed the most), it is highly unlikely that for the “median” patient the AUCs measured herein will have any positive impact on the infection outcome. Indeed, suboptimal exposure might lie behind reported failures of inhaled polymyxins to objectively improve clinical outcomes [ 8 , 26 ].…”
Section: Discussionmentioning
confidence: 99%